Attitudes of Medical Students and Staff toward Organ Donation in Cases of Brain Death: A Survey at Shiraz University of Medical Sciences. (March 2014) - Zahmatkeshan, Mozhgan; Fallahzadeh, Ebrahim; Moghtaderi, Mozhgan; Najib, Khadijeh-Sadat; Farjadian, Shirin
Context: Organ transplant is one of the most important management strategies for end-of-life patients. The demand for organs in patients awaiting transplant is increasing, and many of these patients die before a donor is found. Objective: To determine the attitudes of medical students and staff at clinical institutions affiliated with a large medical university in the Eastern Mediterranean region toward organ donation in cases of brain death. Participants: A total of 500 medical students, physicians, and nurses recruited at hospitals and medical centers affiliated with Shiraz University of Medical Sciences in Shiraz, Iran. Design and Setting: Information about participants' demographic characteristics, knowledge of organ donation, and willingness to donate their own organs after death was collected by using self-administered questionnaires. Results: Most participants (78%) had favorable attitudes toward donating their own organs after brain death. However, only about 25% of them carried an organ donation card. In addition to public media, the main sources of information about organ donation after brain death were their professors and textbooks. An association in charge of improving public awareness and facilitating the process of registration and issuance of donation cards appears to be necessary.